TRAUMA DALAM NOVEL YU ZHEN - Livia Vasantadjaja (Universitas Dian Nuswantoro, 2017)
ã€Šä½™éœ‡ã€‹Yu Zhen or After Shock (2006) is a novel written by Zhang Ling, a Chinese woman writer who lives in Canada now. After ShockÂ  is a story about the great earthquake happened at Tangshan city, Hebei province, P.R.C in 1976. One interesting point to discuss from this novel is about Wan Xiaodengâ€™s emotional states and conditions as a main character, as well as an earthquake victim in this novel. Wan Xiaodeng not only suffers from physical trauma, but also suffers from acute psychological trauma.This psychological trauma existed from her childhood to adulthood. By psychological point of view, this writing is going to discuss Wan Xiaodengâ€™s symptoms of post traumatic stress disorder, and impacts or responses to the surroundings. Keywords:ã€Šä½™éœ‡ã€‹Yu Zhen, After Shock, Zhang Ling, trauma Â